First experimental investigation of Th4+ doped barium cerate as electrolytes for intermediate-temperature solid oxide fuel cells. Issue 15 (15th November 2016) - Tao, Zetian; Wang, Yaxing; Wang, Yanlong; Diwu, Juan; Chai, Zhifang; Wang, Shuao
Abstract: Barium cerate doped with tetravalent Th is successfully synthesized by a traditional Pechni method. The BaCe0.7 Th0.1 Y0.2 O3−δ (BCT71) composites were applied to an anode supported coin single cell consisting of Ni-BCT71 anode/BCT71 electrolyte/ BCT71-La0.7 Sr0.3 FeO3−δ cathode. The assembled cell is tested from 600 °C to 700 °C with humidified hydrogen (∼3% H2 O) as the fuel and the static air as the oxidant. An open-circuit potential of 0.93 V and a maximum power density of 104 mW cm −2 are obtained for the single cell with an interface resistance of 0.98 Ω cm 2 at 700 °C.